Analyzing practice pattern in treating partial-thickness rotator cuff tears: a dual perspective from national database and American Shoulder and Elbow Surgeons PARCIAL research group - H. Mike Kim, MD; Emily Leary, PhD; Champ L. Baker, 3rd, MD; Leslie A. Barnes, MD; R. Alexander Creighton, MD; Frances Cuomo, MD; Matthew J. DiPaola, MD; Abdullah Foad, MD; James M. Gregory, MD; Brian F. Grogan, MD; Scott G. Kaar, MD, MBA; Eitan M. Kohan, MD; et al. (JSES International)
Background: Partial-thickness rotator cuff tears (PTRCTs), often considered less severe than full-thickness rotator cuff tears (FTRCTs), can be equally symptomatic. Despite the prevalence of PTRCTs, scholarly attention has predominantly focused on FTRCTs, resulting in a relative neglect of PTRCTs. This study aimed to assess the incidence of surgical repairs for PTRCTs in the United States (U.S.) using the Nationwide Ambulatory Surgery Sample (NASS) database and delineate practice patterns among a group of American Shoulder and Elbow Surgeons (ASES) members. Methods: The NASS database, representing approximately 67% of U.S. ambulatory surgical encounters, was queried to obtain the incidence of PTRCT and FTRCT repairs for the year 2019. Data on patient sex, hospital location, setting, teaching affiliation and size, and primary payor were also obtained. Separately, a retrospective chart review was conducted by 13 ASES research group members, collecting data on rotator cuff repairs performed from July 2021 to June 2022 at their individual institutions. Collected data included age, sex, extent and type of rotator cuff tears, duration of symptoms prior to surgical repair, and type and duration of nonoperative treatment. Results: The NASS database showed that PTRCT repairs accounted for at least 23% of the 187,787 rotator cuff repairs performed in 2019, with potential underestimation due to unspecified tear categorization. The retrospective chart review of the ASES research group revealed that PTRCT repairs constituted 27.8% of all rotator cuff repairs with substantial variability among institutions (8.6%-67.1%), that nonoperative measures were commonly employed, with a mean 12-month duration before surgical repair, and that the most common type of nonoperative treatment was supervised physical therapy combined with corticosteroid injection (37.7%). Discussion: This study revealed approximately one-fourth of all rotator cuff repairs conducted in the U.S. were attributed to PTRCTs with substantial variability in proportion of PTRCT repairs across individual orthopedic practices. The overall duration of nonoperative treatment was consistent with the existing literature. This study provides insights into the landscape of PTRCT repairs and associated practice patterns. Further investigation into factors influencing treatment decisions is warranted.